Out-of-hospital cardiac arrest with Do-Not-Resuscitate orders signed in hospital: Who are the survivors?. (June 2018) - Zhang, Wanwan; Liao, Jinli; Liu, Zhihao; Weng, Rennan; Ye, Xiaoqi; Zhang, Yongshu; Xu, Jia; Wei, Hongyan; Xiong, Yan; Idris, Ahamed
Abstract: Background: Signing Do-Not-Resuscitate orders is an important element contributing to a worse prognosis for out-of-hospital cardiac arrest (OHCA). However, our data showed that some of those OHCA patients with Do-Not-Resuscitate orders signed in hospital survived to hospital discharge, and even recovered with favorable neurological function. In this study, we described their clinical features and identified those factors that were associated with better outcomes. Methods: A retrospective, observational analysis was performed on all adult non-traumatic OHCA who were enrolled in the Resuscitation Outcomes Consortium (ROC) PRIMED study but signed Do-Not-Resuscitate orders in hospital after admission. We reported their demographics, characteristics, interventions and outcomes of all enrolled cases. Patients surviving and not surviving to hospital discharge, as well as those who did and did not obtain favorable neurological recovery, were compared. Logistic regression models assessed those factors which might be prognostic to survival and favorable neurological outcomes at discharge. Results: Of 2289 admitted patients with Do-Not-Resuscitate order signed in hospital, 132(5.8%) survived to hospital discharge and 28(1.2%) achieved favorable neurological recovery. Those factors, including witnessed arrest, prehospital shock delivered, Return of Spontaneous Circulation (ROSC) obtained in the field, cardiovascular interventions or procedures applied, and no prehospital adrenaline administered, were independently associated with better outcomes. Conclusions: We suggest that some factors should be taken into considerations before Do-Not-Resuscitate decisions are made in hospital for those admitted OHCA patients.